Perbandingan Efektivitas Antibakteri Ekstrak dan Sediaan Hand Soap Gel Daun Peppermint (Mentha piperita L.) Terhadap Bakteri Staphylococcus aureus Penyebab Infeksi Kulit - Candrika Candrika; Nufadila Nazmi; Halimah Raina Nasution; Ziza Putri Aisyia Fauzi; Khaira Banu; Lusi Mardika Ariyanti; Hardiyanti Rukmana (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Peppermint leaves (Mentha piperita L.) contain various secondary metabolites, including flavonoids, alkaloids, tannins, and steroids, which exhibit antibacterial activity. The development of peppermint extract into a hand soap gel requires evaluation of its physical stability and antibacterial effectiveness. Aim: This study aimed to formulate a hand soap gel from peppermint leaf ethanol extract and evaluate its physical characteristics, stability, and antibacterial activity against Staphylococcus aureus. Methods: Peppermint leaves were extracted by maceration using 70% ethanol. Hand soap gel formulations containing 3%, 6%, and 9% extract concentrations were prepared and evaluated through organoleptic, homogeneity, spreadability, foam height, pH, viscosity, and stability tests under different storage temperatures. Antibacterial activity was determined against Staphylococcus aureus using the agar diffusion method. Results: The ethanol extract demonstrated antibacterial activity with a maximum inhibition zone of 17.1 mm at 50% concentration. All hand soap gel formulations showed good physical characteristics and stability under various storage temperatures. The antibacterial activity of the formulations increased with extract concentration, producing inhibition zones ranging from 20.8 to 21.1 mm, categorized as very strong activity. Statistical analysis using one-way ANOVA showed significant differences among treatment groups (p < 0.05). Conclusion: Peppermint leaf ethanol extract can be successfully formulated into a stable hand soap gel preparation with very strong antibacterial activity against Staphylococcus aureus.